Partial north-northwestern Australian origin of the Malesian flora - MOSMAN, JASPER MARTIJN; PETER CORNELIS VAN WELZEN (Reinwardtia, 2025)
The current study aims to see if a dispersal pathway existed between northern/ northwestern Australia and the Lesser Sunda Islands and Southern Moluccas by using distributional data of plants, dated phylogenies and historical biogeography. Dispersal between Asia and Australia has already been shown to exist, especially through Northern Queensland and New Guinea into the Malay Archipelago (Malesia). Taxa occurring in the Northern Territory and Western Australia were compared to taxa present in the Lesser Sunda Islands and Southern Moluccas as a means to explain the origin of part of the Malesian flora. Distribution data of taxa were collected from the Global Biodiversity Information Centre and the database of Naturalis Biodiversity Center, reviewed for accepted names and distribution data via Kew Gardens’ Plants of The World Online and dated phylogenies were traced via Google Scholar. The resemblance in genus and species lists between Western Australia/Northern Territory and the Lesser Sunda Islands/southern Moluccas indicates a floral exchange, likely, mainly from Australia to Malesia. Historical biogeographic data were found in only two instances, showing a dispersal to the Lesser Sunda Islands/southern Moluccas around 5 Ma. The conclusion is that this pathway did not result in a major influx of flora into the Malesian area.